MAKNA KONSEPTUAL DAN MAKNA ASOSIATIF NARASI IKLAN ROKOK DI TELEVISI - Arsyad, Huzaefah; Rijal, Syamsul; Rokhmansyah, Alfian (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
The purpose of this study is to describe the conceptual and associative meanings of cigarette advertising narratives on television. Research conducted in this research is descriptive qualitative research and includes library research. The data collection technique used is the listening technique which discusses the skill of engaging in engaging, recording techniques, and note taking techniques. The data analysis technique used is the basic PUP technique used to understand associative and conceptual meanings in each clause in the narrative of cigarette advertisements on television. From the results of the study found seven advertisements. From the seven narratives, it has been divided into several parts to form clauses, phrases and sentences so that 35 data are obtained which are then described based on conceptual and associative meanings. The embodiment of conceptual meaning in cigarette advertisement narratives on television consists of seven narratives that contain conceptual meanings, namely (1) A Mild Version of the Cigarette Ad Function takes 14 words; (2) Define Your Style (Make Possible) Version of the advertisement of the Dunhil Cigarette is 22 words; (3) Surya Pro Mild (We are Stonger) cigarette ad captures 10 words; (4) Sampoerna U Bold Filter (five-rain rain) ad protector; (5) Lightweight Cigarette Ads (Pure Taste) arrested 12 words; (6) White & Black version of the Malboro Mild Black Cigarette Ad in 15 words; and (7) the successful version of Wismilak Diplomat Cigarette Ad won 22 words. The embodiment of associative meaning in cigarette advertisement narratives on television consists of seven narratives that contain associative meanings, namely (1) A Mild Version of Advertisements A Function of Cigarettes takes 12 words; (2) Dunhil Cigarette Advertisement Version Define Your Style (Make Possible) A combination of 8 words; (3) Surya Pro Mild (Kami Stonger) Cigarette Ad catches three words; (4) Sampoerna U Bold Filter (Rain Water Only) Cigarette Advertising; (5) Lightweight Cigarette Ads (Pure Taste) like five words; (6) White & Black version of the Malboro Black and Black Cigarette Advertisement four-word donation; and (7) the successful version of the Wismilak Diplomat Cigarette Ad seizes freedom of words.